Role of sclerotherapy in management of low flow vascular malformations - Kaur, Manpreet; Sachdeva, Parul; Syal, Rajan; Singh, Savijot (International Surgery Journal, 2021)
Background: Low flow vascular malformations are most common in the head and neck region. Only symptomatic malformations require treatment. Sclerotherapy followed by surgery was considered the gold standard treatment but in the head and neck region, it may produce cosmetic and physiological defects. In the present study, multiple injections of sclerotherapy with 3% sodium tetradecyl sulphate was used for the treatment of low flow vascular malformations. Methods: Twenty cases of low flow vascular malformations of the oral cavity who presented in the outpatient department of ESIC Model Hospital, Ludhiana from 2014-2016 were selected for the study. Only significantly sized (>4 cm) and easily accessible lesions were included. Staged sequential sclerotherapy with 3% STS under strict fluoroscopy control was used as the sole treatment. Results: A total of 20 patients were taken of which, 25% required three sessions, 65% five to six sessions each and 10% required eight sessions each. All patients showed good results with complete regression and no mucosal ulceration. Conclusions: Staged sequential sclerotherapy with 3% STS should be the treatment of choice in low flow vascular lesions involving mucosal and cutaneous structures of head and neck region especially anterior two-thirds of tongue, palate, gingiva, buccal mucosa and lips. Surgical removal may affect critical neurovascular structures and cause cosmetic deformity. So the removal is advisable in life-threatening conditions, lesions requiring general anaesthesia and single sitting removal.